Democratic control of Romanian intelligence after three decades: quis custodiet ipsos custodes?. Issue 4 (2nd October 2018) - Zulean, Marian; Şercan, Emilia
ABSTRACT: Romania faced one of the most dramatic transitions from authoritarian communism to become a democracy and a member of the North-Atlantic Treaty Organization (NATO) and the European Union (EU). The backbone of building a democratic society has been civilian control of the military. This article briefly describes the norms and institutions of democratic control of the intelligence services in Romania and assesses how the mechanisms of democratic control have worked in practice after almost three decades of reform. We argue that many of the post-1989 reforms have been only superficial implemented and monitored, particularly after Romania joined NATO and the EU. The article concludes that the democratic control of intelligence in Romania is an unfinished business. There are structural shortcomings embedded in the process of democracy consolidation that need to be addressed.